Partial versus Productive Immunoglobulin Heavy Locus Rearrangements in Chronic Lymphocytic Leukemia: Implications for B-Cell Receptor Stereotypy - Tsakou, Eugenia (ScholarOne, 2011)
The frequent occurrence of stereotyped heavy complementarity-determining region 3 (VH CDR3) sequences among unrelated cases with chronic lymphocytic leukemia (CLL) is widely taken as evidence for antigen selection. Stereotyped VH CDR3 sequences are often defined by the selective association of certain immunoglobulin heavy diversity (IGHD) genes in specific reading frames with certain immunoglobulin heavy joining (IGHJ ) genes. To gain insight into the mechanisms underlying VH CDR3 restrictions and also determine the developmental stage when restrictions in VH CDR3 are imposed, we analyzed partial IGHD-IGHJ rearrangements (D-J) in 829 CLL cases and compared the productively rearranged D-J joints (that is, in-frame junctions without junctional stop codons) to (a) the productive immunoglobulin heavy variable (IGHV )-IGHD-IGHJ rearrangements (V-D-J) from the same cases and (b) 174 D-J rearrangements from 160 precursor B-cell acute lymphoblastic leukemia cases (pre-B acute lymphoblastic leukemia [ALL]). Partial D-J rearrangements were detected in 272/829 CLL cases (32.8%). Sequence analysis was feasible in 238 of 272 D-J rearrangements; 198 of 238 (83.2%) were productively rearranged. The D-J joints in CLL did not differ significantly from those in pre-B ALL, except for higher frequency of the IGHD7-27 and IGHJ6 genes in the latter. Among CLL carrying productively rearranged D-J, comparison of the IGHD gene repertoire in productive V-D-J versus D-J revealed the following: (a) overuse of IGHD reading frames encoding hydrophilic peptides among V-D-J and (b) selection of the IGHD3-3 and IGHD6-19 genes in V-D-J junctions. These results document that the IGHD and IGHJ gene biases in the CLL expressed VH CDR3 repertoire are not stochastic but are directed by selection operating at the immunoglobulin protein level.